Biochemical and Serological Characterization of Hydrogen Sulfide-Positive Variants of Escherichia coli - Darland, Gary (1974)
Over 200 H(2)S-positive, gram-negative rods have been characterized by standard biochemical and serological techniques. The results indicate that the isolates are H(2)S-positive variants of Escherichia coli. Comparison of the variants with biochemically typical E. coli suggests that they represent a rather limited subgroup within the species. The H(2)S-positive strains were more resistant to antibiotics than the typical strains; 54% of the H(2)S-positive isolates were resistant to three or more antibiotics compared with only 25% of the typical strains. Similar differences were also seen in the distribution of O and H antigens and in the results of certain biochemical tests.